A Meta-Analysis of Cardiovascular Events in Systemic Lupus Erythematosus. (4th July 2019) - Gu, Ming-Ming; Wang, Xue-Ping; Cheng, Qian-Yao; Zhao, Yu-Lan; Zhang, Tian-Ping; Li, Bao-Zhu; Ye, Dong-Qing
ABSTRACT: Objective : To identify accurate occurrence and risk of cardiovascular (CV) events (stroke and myocardial infarction [MI]) in patients with systemic lupus erythematosus (SLE). Methods : Systemic literature search in PubMed and additional manual search were performed to obtain interested studies until March 31, 2018. The pooled incidences and risk of stroke and MI were calculated. Results : A total of 24 studies were included in this meta-analysis. For MI, a total of 1, 516 SLE patients were reported to had MI (n = 96, 154) over a mean follow-up of 9.98 years: incidence 2.0% (95% CI: 1.7–2.4%), i.e. 0.20/100 pyrs; in the five studies, 360 SLE patients (n = 18, 943) and 817 controls had MI (n = 111, 525), revealing that the risk of MI in SLE population was 3.04 times higher than in the general population (RR = 3.04, 95% CI: 1.81–5.11). For stroke, the incidence of 17 studies during the 10.09 follow-up period using random model was 4.4% (95% CI: 3.6–5.1%), i.e. 0.44/100 pyrs; in the 7 studies, 694 SLE patients (n = 22, 594) and 4, 034 controls had stroke (n = 255, 023), indicating that the risk of MI in SLE population was 1.95 times higher than that in the general population (RR = 1.95, 95% CI: 1.52–2.53). Conclusion : Based on the findings from previous reports, our meta-analysis showed that patients with SLE have been at higher risk of CV events.